Presentation, morbidity and treatment outcome of acromegaly patients at a single centre - Rayees Ul Hamid Wani; Raiz Ahmad Misgar; Moomin Hussain Bhat; Javaid Ahmad Bhat; Shariq Rashid Masoodi; Mir Iftikhar Bashir; Arshad Iqbal Wani (Indian Journal of Endocrinology and Metabolism, 2019)
Introduction: The management of acromegaly, a rare and potentially curable disease, has undergone a paradigm shift in the past few decades. Many of the treatment modalities recommended for acromegaly are either too expensive or not available in many parts of India. There is a dearth of treatment and outcome data in Indian patients. Aim: Our aim was to study the clinical presentation, hormonal profile, radiology, management, and outcome of the disease at our center. Materials and Methods: Fifty one patients with acromegaly who attended the Department of Endocrinology, SKIMS, Srinagar, between October 2015 and April 2017, were included in the study. Clinical and hormonal profiles, comorbidities, treatment modalities, and outcome were evaluated. Results: The gender distribution was equal with the mean age of 42.3 ± 10.9 years at diagnosis. The majority (41) of the patients had macroadenoma. The most common presenting manifestations were acral enlargement and headache. Hypertension was present in 23, musculoskeletal manifestations in 19, and diabetes mellitus in 11 patients. Surgery was the most common method of treatment. Preoperatively only one patient with micro-adenoma had hypocortisolism, which was persistent in postoperative period, while no patient had preoperative or postoperative hypothyroidism or hypogonadism. As per the present consensus criteria, 23.7% patients achieved disease control (40% with microadenoma and only 19.5% with macroadenoma). The surgical complications occurred in 5 patients–CSF leak in 3 meningitis in 2 patients all except one having macroadenoma. Conclusions: The presentation of disease was generally comparable to that reported in literature. Cure rates were significantly lower than those reported from many large centers.